New stories, same Stigma: Framing analysis of news articles about people with alcohol-related conditions needing liver transplants - Whitney Langlee; Divya Kalluri; Rivka Abedon; Aura T. Teles; Janetta Brundage; Po-Hung Chen; Andrew M. Cameron; Hannah C. Sung; Olivia S. Kates (SSM: Qualitative Research in Health)
Background: Public stigma surrounding alcohol use disorder (AUD) negatively impacts people with alcohol-related liver disease (ALD) in need of liver transplants (LT). Representations of LT for ALD are socially constructed in part through media, but media on this topic has been underexplored in current research. Methods: Research team members conducted systematic searches during 7/2022-5/2024 for online, publicly available articles about LT for ALD within leading English-language news sites in the US by monthly visits (n = 24). Using inductive framing analysis, we coded and identified patterns in news articles (n = 42) from 1990 to 2021 to generate frames. Findings: Our inductive analysis generated 4 main frames: (a) making individual exceptions: good people in a bad group, (b) appealing to societal costs: individual actions putting a strain on society, (c) questioning professionals' judgements: doctors’ discretionary power, and (d) portraying healthcare as a competition: unfair play in a zero-sum game. Media characterized people with ALD as less deserving of liver transplant, but with individual exceptions. Articles described people with “self-induced” illnesses as irresponsible towards themselves, other LT candidates, and society; doctors as “gatekeepers” with discretionary power over how to apply criteria or rules; and the liver transplant waitlist as a competitive zero-sum game in which people with ALD are or should be deprioritized. Discussion: News articles reflect our society's stigmatization of alcohol-related conditions as well as misconceptions about transplant listing and allocation. Such mischaracterizations can further marginalize stigmatized patients with alcohol-related conditions in need of LTs. We offer recommendations for public communications, including avoiding representations of patients with ALD as exceptions to the norm and contextualizing LT for ALD within the context of public health and social and systemic factors.